Síntese e caracterização de lipossomas funicionalizados com LQM168 e quantum dots - Lins, Samaysa de Lima (2020)
The pharmaceutical industry has been investing in the development of new strategies for obtaining drugs and pharmaceutical forms safer and effective to promote more effective chemotherapy for the patient. A new strategy that stands out is the development of hybrid molecules for providing an improved pharmacological effect and a decrease in toxicity; another strategy is the association of drugs with carrier systems in order to promote an improvement in the physicochemical properties of the molecules as well a targeted delivery. To increase the solubility and stability of LQM168 (which presents quinoline and thiazolidine nuclei with proven antitumor activity), the presente work aims to synthesize liposomes and liposomes functionalized with CdSe/CdS, associate with LQM168 and evaluate the formation of conjugates by microscopic, spectroscopic and electrochemical techniques. The cationic unilamellar liposomes and conjugates studied were synthesized by the hydration of lipid films method and characterized using AFM, UV-VIS and FTIR. Electrochemical studies for LQM 168 were performed in aprotic medium (DMF+TBAP) and in protic medium (PBS pH 7.0) in electrochemical system consisting on 3 electrodes (working electrode: glassy carbon; reference electrode: Ag|AgCl|Cl-; counter electrode: platinum wire). In VC studies, LQM 168 presented a reversible electrochemical profile with redox potential values favorable to physiological electron transfer processes (Eap: -0.056V and Ecp: -0.085V). In the behavior of LQM168 against ssDNA and dsDNA by VPD, an interaction of LQM168 with the guanine and adenine bases was observed without causing the DNA double strand break; in the presence of oxygen, LQM168 did not promote the generation of ERO’s. Interaction studies between LQM168 and liposomes by UV-VIS presented the band supression at 315nm and a batochromic and hypochromic band shift at 415nm; the complex formation was confirmed by FTIR due to a band supression at 815cm-1 for the C-Cl stretching and the permanence of the band at 1477cm-1 for the methyl in the position 4 of the ring. Cationic unilamellar liposomes are a promising alternative to overcome the physicochemical factors of LQM168 allowing increased stability and solubility in aqueous medium; The use of electrochemical techniques enable to propose a redox mechanism for LQM168, to classify the electrochemical behavior and the electrodic processes that occurred, as well to evaluate possible mechanisms of action that may be associated with the molecule.